Pendekatan Monodisipliner dalam Pengembangan Keilmuan dan Implikasinya Pada Integrasi Keilmuan - Laily Faridhatun Nikmah; Ngainun Na'im; Akhyak Akhyak (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Determining a monodisciplinary strategy for the advancement of science and its use in scientific integration is the aim of this research. This research uses a certain type of library research. To conduct descriptive research, researchers use words and not lists of data. These words can basically provide a general overview or explain current problems and their solutions. Content analysis is the data analysis method used, and places high priority on explaining the content of various existing propositions that arise from various theories and previous analyzes carried out by other researchers. The research findings show that a monodisciplinary approach is an approach whose foundation is solely on the scientific subject in question, without merging or combining it with other scientific fields. All sciences operate under monodisciplinary supervision, support, and motivation. Monodisciplinarity itself regulates scientific research and theoretical conclusions. A narrowly focused approach to science will result in a narrow view of religion and an interpretation of religion that has nothing to do with the research environment. The urgency of this interdisciplinary study is achieved by creating a paradigm that needs to be implanted in society by: Switching from a format based on formalism to a substantive format, changing universalism from exclusivism, research, study, and improvements both internal and external (inside and outside).